Sieciowe "zapadanie się" wartości przedsiębiorstwa - Perechuda, Kazimierz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents: - the essence of the company's value, - the impact of the net enterprises on value creation, - the difficulties in measuring the value of the net companies, - the changing role of the knowledge workers in the value creation in the net enterprises. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 380-386